Fecal secretory immunoglobulin a, human ß defensin-2, and calprotectin levels in preterm neonates who consumes breast milk only, formula milk only, and combination - Eko Sulistijono; Putri Primawardani; Rusdian N. Ningsih; Bernardinus P.A. Pradipta (Medical Faculty of Brawijaya University, Indonesia, 2022)
Background: Secretory immunoglobulin A, human ß-defensin2 and calprotectin play an essential role in digestive system defense. This study aims to assess fecal SIgA, hBD-2, and calprotectin in preterm neonates (as inflammation marker) with different feeding patterns. Method: This study was cohort designed included 39 preterm neonates, which were categorized into breast milk only, formula milk only, and combination. Fecal SIgA, hBD-2, and calprotectin measured by ELISA. Results: Fecal SIga in the breast milk only group were significantly higher (p<0.005). Fecal HBD-2 and calprotectin in the formula milk only group were highest but not significantly different (p=0.463) with the combination group. Conclusion: Fecal SIgA levels that consumed breast milk only were significantly higher. Fecal HBD-2 and calprotectin levels that consumed formula milk only were highest but not significantly different from the combination group.